Rapid Acquisition of Immunologic Tolerance to Factor VIII and Disappearance of Anti-factor VIII IgG4 After Prophylactic Therapy in a Hemophilia A Patient With High-titer Factor VIII Inhibitor. Issue 4 (May 2015) - Moorehead, Paul C.; Thibeault, Lisa; Tuttle, Angie; Grabell, Julie; Dwyre, Louise; Silva, Mariana; James, Paula; Lillicrap, David
Abstract : We report an 11-month-old boy with severe hemophilia A who had regular exposure to factor VIII (FVIII) intended to reduce the risk of developing an inhibitor. He developed a high-titer inhibitor (peak titer 19 BU) that disappeared within 6 weeks of starting immune tolerance induction (ITI). Anti-FVIII IgG4 peaked briefly compared with anti-FVIII IgG1 and the Bethesda titer. Neither rapid resolution of an inhibitor after prophylaxis nor this behavior of anti-FVIII IgG4 has been previously reported. Transient anti-FVIII IgG4 may be a marker of an attenuated anti-FVIII response induced by prophylactic FVIII therapy.